Numerical Simulation of Thermal Field in Mass Concrete With Pipe Water Cooling - Zhu, Fuxian; Chen, Guorong; Zhang, Feng; Li, Qingwen (Frontiers in Physics, 2021)
Water pipe cooling is mainly used to control temperature in the construction of mass concrete structures. It is important to reveal how to accurately stimulate the temperature field of mass concrete under action of this water pipe cooling. This paper presents a new method for this purpose. In this method, the contact surface of the water pipe and the concrete is used as the heat dissipation surface into the control equation and the composite Multiquadrics radial basis function (MQ-RBF) and low-order linear polynomial combination are used to discrete the spatial domain. The heat dissipation surface of the water pipe is included in the boundary conditions so that there is no need to build the refined water pipe modeling. This new method not only reduces the calculation cost but also ensures calculation accuracy. Through four calculation examples, this paper show that the algorithm has advantages in the numerical simulation of the concrete temperature field with water pipe cooling.